2020
DOI: 10.3390/ani10112183
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Folic Acid Supplementation Differently Affects the Small Intestinal Phenotype and Gene Expression of Newborn Lambs from Differing Litter Sizes

Abstract: The purpose of this study was to investigate the effect of maternal dietary folic acid (FA) supplementation during gestation on small intestinal development of newborn lambs of different litter sizes, focusing on the intestinal morphology and development-, apoptosis- and digestion-related genes expression. One hundred and twenty Hu ewes (Ovis aries) were inseminated and randomly allotted to three groups. One group received a control diet [without FA supplementation, control (CON)] and the other two groups rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Besides folic acid plays an important role in increasing the expression of mRNA in the cells. It can cause an increase in the growth and proliferation of cells and thus an increase in the length of the villi and this is was observe on after folic acid administration as compare with before folic acid administration (Li et al, 2020). Immune tolerance of IGg of ND showed a significant (p≤0.05) increase after administration of folic acid when compared with before administration of folic acid.…”
Section: Resultsmentioning
confidence: 81%
“…Besides folic acid plays an important role in increasing the expression of mRNA in the cells. It can cause an increase in the growth and proliferation of cells and thus an increase in the length of the villi and this is was observe on after folic acid administration as compare with before folic acid administration (Li et al, 2020). Immune tolerance of IGg of ND showed a significant (p≤0.05) increase after administration of folic acid when compared with before administration of folic acid.…”
Section: Resultsmentioning
confidence: 81%
“…Contrary to the findings ofWang et al (2021b),Liu et al (2011) reported that FA supplementation did not affect the intestinal morphology, including the VH and CD. A previous finding observed that increasing maternal FA supplementation significantly enhanced the ratio of small intestinal weight to live body weight and the thickness of the intestinal muscle layer in the offspring(Li et al 2020). Variation in results might be as a result of different FA inclusion levels and species used.…”
mentioning
confidence: 88%
“…Researchers have recently evaluated the effects of maternal folic acid supplementation throughout gestation on small intestinal mRNA expression of SI, MGAM, and LCT in lambs from differing litter sizes [ 51 ]. The study was designed with a 2 × 3 factorial arrangement of treatments where folic acid was supplemented throughout gestation at 0, 16, or 32 mg/kg of diet DM.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
“…After parturition, lambs from twin-bearing and triplet-bearing ewes were slaughtered for tissue collection. There was a folic acid supplementation × litter size interaction where maternal folic acid supplementation had a quadratic effect on duodenal LCT expression in twins, but no effects in triplets [ 51 ]. Additionally, duodenal SI expression was greater in triplet-born lambs compared to twin-born lambs.…”
Section: Influence Of Prenatal Nutrition On Fetal Carbohydrase Actmentioning
confidence: 99%
See 1 more Smart Citation